Model Peningkatan Loyalitas Pelanggan dengan Pengujian terhadap Servicescape, Kualitas Pelayanan dan Kepuasan Pelanggan - Marno Nugroho; Sahrul Romadhon (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2018)
In the era of globalization, the development of the fashion world with a variety of models and designs is increasing very rapidly. This condition has triggered a cycle of changing the style of dress that is dynamic, especially in the watch fashion industry. In addition to referring to the time the watch can also give a distinctive impression to the wearer. The sampling method is carried out using non probability sampling techniques by means of purposive sampling. By wearing a watch we can look more elegant. With a fairly large number of competitors, triggering the clock shop to focus on product quality and price competition, but the competition is not enough because there are still many aspects that can be used by the clock store to win the competition and become a market leader. Innovative strategies are needed to survive and win the competition, including strategies to improve service quality and rearrange Servicescape in this regard with regard to customer satisfaction and customer loyalty.